2001
DOI: 10.1520/jfs14911j
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of Changing Ammunition on the Composition of Organic Additives in Gunshot Residue (OGSR)

Abstract: The measurement of the organic additives in smokeless gunpowder is an attractive approach for the detection of handgun use because it provides compositional information that can help associate residues and unfired gunpowder. We investigate several factors that will be required to advance the characterization of organic gunshot residue (OGSR) as a useful forensic tool, including evaluating residue contamination from previously fired ammunition, particle-to-particle compositional variability, and compositional f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Similar to Andrasko, MacCrehan et al found that compositional analysis of the propellant provides information that can associate residue samples with unfired gunpowder [89,90,91,92]. It was reported that qualitative identification and quantitative determination of additives in gunpowder enabled calculation of a numerical propellant (NG) to stabilizer ratio (P/S) that might be a useful index in associating handgun-fired gunpowder residues with unfired powder.…”
Section: Gunpowder Residue Analysismentioning
confidence: 92%
See 1 more Smart Citation
“…Similar to Andrasko, MacCrehan et al found that compositional analysis of the propellant provides information that can associate residue samples with unfired gunpowder [89,90,91,92]. It was reported that qualitative identification and quantitative determination of additives in gunpowder enabled calculation of a numerical propellant (NG) to stabilizer ratio (P/S) that might be a useful index in associating handgun-fired gunpowder residues with unfired powder.…”
Section: Gunpowder Residue Analysismentioning
confidence: 92%
“…MacCrehan et al [56,57,88,89,90,91,92] used MECE for analysis and comparison of fired and unfired propellants. Procedures for recovery of gunpowder residue components under a variety of sampling conditions were evaluated and improved for MECE analysis.…”
Section: Gunpowder Residue Analysismentioning
confidence: 99%
“…MEKC analysis of the organic additives in smokeless gunpowders was also used by McCrehan et al to evaluate residue contamination from previously fired ammunition. Compositional analysis of the residues showed only trace of the previously fired powder in the first shot and none in the subsequent shots [62]. Also, MEKC was used to test a new method for organic gunshot residue collection by hair combing.…”
Section: Explosive Analysis and Gunshot Residuesmentioning
confidence: 99%
“…MacCrehan and co-workers have pioneered the development of CE for the detection of organic gunshot residue and smokeless powders. In a series of papers they have demonstrated the applicability of CE for the detection of smokeless powder residue from pipe bombs [41], and gunshot residue [42][43][44]. These papers consist of a series of different validation studies of the analysis of smokeless powders.…”
Section: Explosives Residue Gunshot Residue Ink and Dye Analysismentioning
confidence: 99%